Optimized Jasmonic Acid Production by Lasiodiplodia theobromae Reveals Formation of Valuable Plant Secondary Metabolites - Eng, Felipe; Haroth, Sven; Feussner, Kirstin; Meldau, Dorothea; Rekhter, Dmitrij; Ischebeck, Till; Brodhun, Florian; Feussner, Ivo (PLOS ONE, 2016)
Jasmonic acid is a plant hormone that can be produced by the fungus Lasiodiplodia theobromae via submerged fermentation. From a biotechnological perspective jasmonic acid is a valuable feedstock as its derivatives serve as important ingredients in different cosmetic products and in the future it may be used for pharmaceutical applications. The objective of this work was to improve the production of jasmonic acid by L. theobromae strain 2334. We observed that jasmonic acid formation is dependent on the culture volume. Moreover, cultures grown in medium containing potassium nitrate as nitrogen source produced higher amounts of jasmonic acid than analogous cultures supplemented with ammonium nitrate. When cultivated under optimal conditions for jasmonic acid production, L. theobromae secreted several secondary metabolites known from plants into the medium. Among those we found 3-oxo-2-(pent-2-enyl)-cyclopentane-1-butanoic acid (OPC-4) and hydroxy-jasmonic acid derivatives, respectively, suggesting that fungal jasmonate metabolism may involve similar reaction steps as that of plants. To characterize fungal growth and jasmonic acid-formation, we established a mathematical model describing both processes. This model may form the basis of industrial upscaling attempts. Importantly, it showed that jasmonic acid-formation is not associated to fungal growth. Therefore, this finding suggests that jasmonic acid, despite its enormous amount being produced upon fungal development, serves merely as secondary metabolite.